Analisis Pengaruh Penambahan GGBFS Sebagai Substitusi Semen Terhadap Kuat Tekan dan Flowability pada Beton SCC - Muhamad Alfidya Wildani; Ahmad Yudi; Ayu Sinta Aprilia (Jurnal Ilmiah Teknologi Infomasi Terapan, 2025)
Self Compacting Concrete (SCC) is a modern concrete innovation that has the ability to flow and compact itself without the help of a vibration device. SCC concrete has almost the same composition as normal concrete, only the difference in the viscosity produced. The use of superplasticizer in SCC concrete is needed to improve the flowability of concrete without reducing the strength of the concrete. The purpose of this study is to analyze the influence resulting from the use of GGBFS as a cement substitution on the value of flowability, passing ability, and compressive strength applied to SCC concrete. The variation of GGBFS used was 0%; 5%; 10%; 15%; 20%; and 25% and the addition of a superplasticizer of 1.2% of the total weight of cement. The planned compressive strength is 40 MPa with the procedure for making concrete referring to SNI 7656 – 2012. The flowability and passing ability tests carried out are slump flow, L-box test, and V-funnel. The test results show that the use of GGBFS will affect the flowability and passing ability and increase the compressive strength as the GGBFS used increases. The maximum compressive strength occurred at a 20% GGBFS variation of 43.687 MPa.